Validity of a taekwondo-specific test to measure VO2peak and the heart rate deflection point - Sant'Ana, J.; Franchini, E.; Murias, J. M.; Diefenthaeler, F. (The Journal of Strength and Conditioning Research, 2019)
This study investigated whether the progressive specific taekwondo test (PSTT) is a valid test to measure peak oxygen consumption (VO2peak) and the heart rate deflection point (HRDP) in taekwondo athletes. Eighteen male black belt athletes (25.3 ± 4.8 years; 8.2 ± 4.7 years of practice; 171.8 ± 4.7 cm; 76.1 ± 8.2 kg, and 13.1 ± 2.9% body fat) involved in regional- and national-level competitions performed the PSTT and an incremental treadmill test (IT). The following variables were analyzed: VO2peak, respiratory quotient, oxygen consumption at the HRDP (VO2HRDP), peak heart rate (HRpeak), HRDP, and peak posttest blood lactate concentration. During the PSTT, the peak kick frequency (FKpeak) and kick frequency at the HRDP (FKHRDP) were also obtained. During the IT, the peak speed and the speed at the HRDP were identified by the Dmax method (the first and last points of the curve were connected by a straight line, and the most distant point of the curve to the line was considered as the HRDP). No differences were observed between VO2 responses during the PSTT and IT (p > 0.05). VO2peak and VO2HRDP presented bias (1.3 ml/kg/min and -0.78 ml/kg/min, respectively) derived from the Bland and Altman plots, with the 95% limits of agreement indicating that the differences between the 2 measures can reach 11% for VO2peak and 17% for VO2HRDP. The PSTT is a valid tool to assess aerobic power and capacity in taekwondo athletes based on direct comparisons to a treadmill test. The test presents more specific variables for the assessment and training of taekwondo athletes, such as FKpeak and FKHRDP, which can be used to determine and control the effects of training and help coaches in prescribing training programs.